2018
DOI: 10.1111/aej.12333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of instrumentation systems on endotoxin reduction from root canal systems: A systematic review of clinical studies and meta‐analysis

Abstract: This systematic review assessed the effect of different root canal instrumentation systems on endotoxin reduction from the root canal system. The literature search was conducted in two electronic databases (PubMed and Scopus) using specific key words. The search strategy followed the PRISMA guidelines. Qualitative synthesis and quantitative synthesis of the data were performed and data interpretation was done based on the guidelines in the Cochrane Handbook. The risk of bias was assessed using Cochrane criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A systematic review has proved that when irrigating regimens are kept constant, the type of instrument used does not have an influence on endotoxin reduction during root canal treatment. 19 Nevertheless, no statistical difference was observed between both instrument systems. Another difference between the protocols of instrumentation evaluated is the final tip diameter of the last instrument used for each system: while HCM presents size #40/04 (step 6), PTN has size #30/07 (X3), which promotes further widening of the zone suggesting greater cleanliness of this region.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A systematic review has proved that when irrigating regimens are kept constant, the type of instrument used does not have an influence on endotoxin reduction during root canal treatment. 19 Nevertheless, no statistical difference was observed between both instrument systems. Another difference between the protocols of instrumentation evaluated is the final tip diameter of the last instrument used for each system: while HCM presents size #40/04 (step 6), PTN has size #30/07 (X3), which promotes further widening of the zone suggesting greater cleanliness of this region.…”
Section: Discussionmentioning
confidence: 91%
“…35 Such a threshold value of the infectious content remains unknown. 19 However, it is expected that in the absence of living gram-negative cells to maintain LPS levels, its action would only be transient and unlikely to impact treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Example 5a : ‘The risk of bias was assessed using Cochrane criteria’ (Neelakantan et al . ). Example 5b : ‘Quality of the included studies was appraised by the revised Cochrane risk of bias tool for randomized trials’ (Pulikkotil et al . ). …”
Section: Explanation and Endodontic Examples Of Items In The Prisma Fmentioning
confidence: 97%
“…The Cone-beam Computed Tomography Analysis has determined the bone destruction and it has been found that pain has a relationship with the number of endotoxins in the root canals [14,15]. Therefore, endotoxin's lessening has been considered one of the vital measures to diminish the total bone destruction [14].…”
Section: Introductionmentioning
confidence: 99%